2022
DOI: 10.1002/vetr.2340
|View full text |Cite
|
Sign up to set email alerts
|

Rate of surgical site and urinary tract infections in dogs after cessation of antibiotics following spinal surgery

Abstract: Background: Excessive use of antimicrobials and the increasing occurrence of antimicrobial resistance are major challenges in both human and veterinary medicine. The role of prophylactic antimicrobial therapy in orthopaedic and neurosurgeries in dogs can be questioned. The aim of this study was to evaluate the rate of surgical site infections (SSI) and urinary tract infections (UTI) in dogs after cessation of antibiotics following spinal surgery. Methods: Electronic patient records from January 2018 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…In a retrospective study by Välkki et al (2020) including 406 dogs undergoing clean orthopedic and neurosurgeries, in which 92.1% of the dogs received prophylactic antimicrobials and 1.1% also received postoperative antimicrobials, the rate of SSIs was 6.3%, suggesting that using only perioperative antimicrobial prophylaxis (without postoperative continuation) does not increase the risk of developing a SSI. In a retrospective study by Korytárová et al (2022) including 158 dogs undergoing neurosurgery, in which all dogs received prophylactic antimicrobials and 58.2% also received postoperative antimicrobials, a similar rate of SSIs in both groups was found (1.1% in dogs receiving postoperative antimicrobials versus 1.5% in dogs only receiving prophylactic antimicrobials).…”
Section: When and For How Long Do Prophy-lactic Antimicrobials Need T...mentioning
confidence: 69%
“…In a retrospective study by Välkki et al (2020) including 406 dogs undergoing clean orthopedic and neurosurgeries, in which 92.1% of the dogs received prophylactic antimicrobials and 1.1% also received postoperative antimicrobials, the rate of SSIs was 6.3%, suggesting that using only perioperative antimicrobial prophylaxis (without postoperative continuation) does not increase the risk of developing a SSI. In a retrospective study by Korytárová et al (2022) including 158 dogs undergoing neurosurgery, in which all dogs received prophylactic antimicrobials and 58.2% also received postoperative antimicrobials, a similar rate of SSIs in both groups was found (1.1% in dogs receiving postoperative antimicrobials versus 1.5% in dogs only receiving prophylactic antimicrobials).…”
Section: When and For How Long Do Prophy-lactic Antimicrobials Need T...mentioning
confidence: 69%
“…Korytárová and colleagues' study is a good example of this effort to reduce the blanket use of prophylactic antimicrobials in surgical patients, as it clearly demonstrates that postoperative antimicrobial therapy is unnecessary in dogs undergoing spinal surgery. 9 However, we can go further and question the necessity of not only…”
mentioning
confidence: 99%
“…For example, a study summarised on p 332 of this issue of Vet Record detected urinary tract infections caused by multidrug-resistant bacteria in 5.1 per cent of dogs following spinal surgery. 9 Furthermore, another study reported SSI caused by multidrug-resistant bacteria in 2.7 per cent of dogs that underwent tibial plateau levelling osteotomy, making revision surgery necessary. 10 Misuse and overuse of antimicrobials are the main drivers in the development of drugresistant pathogens.…”
mentioning
confidence: 99%